Pertanggungjawaban Hukum Atas Pelimpahan Wewenang Dokter Spesialis Kandungan Kepada Bidan - Assegaf, Zulfikar; Nambung, Indar (Jurnal MHKI, 2023)
This study aims to determine the legal responsibility for the delegation of authority of obstetricians to midwives at the Mother and Child Hospital. This research is a normative legal research supported by empirical data. The results showed that the role of an obstetrician and a midwife is very important for patient service. However, the limitation of medical personnel sometimes requires a doctor to delegate authority to midwives to perform a special medical action. Limitations on medical action delegate the authority of doctors to midwives can be seen based on the rules of law governing their respective authorities. Legal responsibility for the process of transferring the authority of obstetricians to midwives includes three legal aspects, namely, civil responsibility, criminal responsibility and administrative responsibility. Both obstetricians and midwives, if proven to have made mistakes in of health services through the delegation authority process, will be responsible for their respective errors (personal liability).